Facing Anxiety, Growing Up. Trait Emotional Intelligence as a Mediator of the Relationship Between Self-Esteem and University Anxiety - Guil, Rocio; Gómez-Molinero, Rocio; Merchan-Clavellino, Ana; Gil-Olarte, Paloma; Zayas, Antonio (Frontiers in Psychology, 2019)
The current study analyzed how trait emotional intelligence (trait EI) mediates the relationship between self-esteem and state anxiety (STAI-S) and trait anxiety (STAI-T). The sample was composed of 153 undergraduate students from the University of Cádiz, Spain (71.9% women and 28.1% men). Students completed measures of self-esteem, STAI-S, STAI-T, and trait EI. Mediation analyses were completed with three trait EI dimensions (emotional attention -EA-, emotional clarity -EC-, and mood repair -MR) as mediating variables, self-esteem as the independent variable, and STAI-S and STAI-T as the dependent ones. Our results confirmed that self-esteem scores explained and predicted both, STAI-S and STAI-T values (13% for STAI-S and 21% for STAI-T). This explanatory capacity is increased by 8% when accounting for all trait EI dimensions. Considering STAI-S, the results of the direct effects showed that a decrease in their levels is predicted through the increases in the levels of both, self-esteem and MR. Regarding STAI-T, the results of the direct effects showed that a decrease in their levels is predicted, in addition to an increment of self-esteem and MR values, by an increase of EC and a decrease of EA. Conversely, indirect effects revealed that higher levels of self-esteem were associated with worse scores in EA and worse MR, which in turn would enhance both STAI-S and STAI-T levels. Moreover, regarding STAI-T higher levels of self-esteem were associated with worse scores in EA and worse EC, therefore increasing STAI-T levels. As shown, the negative association found between self-esteem and EA becomes a key element. The effect of self-esteem on EA and the influence that the latter had on EC and MR exerts an indirect mediated effect with the power to invert the influence that self-esteem wields on both types of anxiety. In this sense, the apparent protective role of self-esteem changed, turning into a risk factor that promotes higher anxiety values.